(untitled) (Raparin Journal of Humanities (RJH), 2026)
This research aims to study the mediating role of entrepreneurial agility in the relationship between strategic physiognomy and strategic excellence, in light of the organizations’ efforts to achieve excellence in their strategies in the current competitive environment to ensure their distinction from competitors, and due to the scarcity of studies that addressed these variables in private universities, therefore, to achieve the research objectives and test its hypotheses, the descriptive analytical approach was used by designing a questionnaire form that was developed by the researchers based on previous literature and after conducting a set of validity and reliability tests in line with the objectives of the current study, and data were collected from (98) leaders in (5) private universities in Sulaymaniyah Governorate, represented by the universities of (Komar, Cihan, Human Development, Tishk, and Goizha). A set of statistical methods, such as dispersion coefficients and structural equation modeling, were used to analyze the data using statistical software (Amos v. 26, SPSS v. 26). The research reached a set of results, the most important of which is the existence of a positive correlation between the study variables (strategic physiognomy, entrepreneurial agility, and strategic excellence), as well as the existence of a significant impact of strategic physiognomy and its dimensions on strategic excellence. In addition, the impact of strategic physiognomy on strategic excellence increases when entrepreneurial agility is present as a mediating variable. Hence, a set of conclusions were indicated that would help in proposing a number of recommendation, the most important of which is the need for private universities to focus on achieving strategic excellence through practicing the dimensions of strategic physiognomy by their leaders, as well as ensuring entrepreneurial agility within them.